Modelling the Inhibition Kinetics of Molybdenum Reduction by the Molybdate-reducing Enterobacter cloacae (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2020)
The mathematical simulation of physical, chemical or biological data can assist a researcher in explaining the physicochemical or biological phenomenon by predicting or estimating the possible actions, to replicate a prediction or retroactivity and to schedule better experiments. Bacteria are an emerging instrument for the bioremediation of the molybdenum pollutant in the world, molybdenum reduction into insoluble molybdenum blue. In this study, the molybdenum reduction rate by the bacterium Enterobacter cloacae was studied for its inhibitory kinetics characteristics using sodium molybdate as a substrate. Modeling kinetics showed that molybdenum reduction could be explained by several models such as Monod, Haldane, Hans-Levenspiel, Luong, Teissier, Aiba and Yano with Aiba as the best model as judged using error function analysis such as bias and accuracy factors (BF and AF), root mean square error (RMSE), adjusted coefficient of determination (adjR2), and corrected Akaike Information Criterion (AICc). The calculated value for the Teissier-Edwardâ€™s constants, which are qmax, Ks, and Ki that are maximal reduction rate, half saturation constant for maximal reduction, half saturation constant for inhibition of reduction were 7.77 (95% C.I.,  4.41 to 19.95) ïmole Mo-blue hr-1, 26.63 (95% C.I.,  12.82 to 40.44) mM and 51.39 (95% C.I.,  23.67 to 79.10) mM, respectively. The true maximal reduction rate, which occurred when the slope of the curve is zero occurs at 36 mM molybdate concentration and a corresponding value of 1.85 ïmole Mo-blue hr-1. The fitting parameters of the Monod model prove a strong bacterial resistance to higher toxic molybdenum levels, making the bacterium useful tool for metals bioremediation work.
Keywords: Bacteria; Monod; Toxicity; Simulation; bioremediation